Communicative Classroom English of Pre-service Teachers - B, Lalitha Devi (Institut Agama Islam Negeri Ponorogo, 2023)
Classroom language shapes the way teachers communicate/ Interact in the classroom. Based on medium of Instruction the teacher has to be aware of the language phrases and expressions appropriate for the classroom situations. The NCF National Curriculum Framework (2005, 2009) of India mentioned the need of classroom English for teachers. The importance of classroom communication is highlighted in the B.ED. syllabuses prepared by the NCERT (National Council for Educational Research and Training) and SCERTs (State Council of Educational Research and Training). The present study considers the need for classroom English for pre-service teachers before they enter the profession. Previous research studies included testing of the classroom English language proficiency of in-service teachers of English subject. In addition to that, current study focuses on pre-service teachers of all subjects and their awareness of classroom English. For this purpose an online test was conducted with 36 pre-service teachers from different B.Ed. Institutions, Telangana and Andhra Pradesh, India. The results indicate that pre-service teachers should be given training to raise their awareness of Communicative English language phrases and expressions used for different classroom situations such as classroom management, content delivery, and feedback. The study has got implications for verbal and non-verbal classroom communication, and use of L2 (Second language) for classroom purposes.